2016
DOI: 10.1515/amm-2016-0210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Microstructural Changes in Aluminium Bronze

Abstract: This paper attempts to summarise the microstructural changes which take place in aluminium bronzes during heat treatment. Another objective of this study was to map the potential of a certain type of aluminium bronzes for undergoing martensitic transformation. The methods, which were chosen for assessing the results of heat treatment with regard to their availability, included measurement of hardness and observation of microstructure using light and scanning electron microscopy, Additional tools for evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Different phases such as α-phase, several κ-phases, and retained β phase are there in Al-bronze. The specific phases also refine the grain structure [47]. Cu-Zn alloy shows a single-phase fcc condition because the level of Zn content is below 35 wt.%.…”
Section: Optical Micrographic Observationmentioning
confidence: 95%
“…Different phases such as α-phase, several κ-phases, and retained β phase are there in Al-bronze. The specific phases also refine the grain structure [47]. Cu-Zn alloy shows a single-phase fcc condition because the level of Zn content is below 35 wt.%.…”
Section: Optical Micrographic Observationmentioning
confidence: 95%
“…However, during a DED-LB process, this precipitation process is suppressed due to the rapid cooling. As a result, a martensitic-like structure is generated (compare Hájek et al [14]) that mainly consists of fine needles in the β'-phase and leads to the elevated hardness of the additive specimen.…”
Section: Microstructure and Mechanical Propertiesmentioning
confidence: 99%
“…Aaltonen et al [11] examined the effect of tempering on the dealloying corrosion resistance of two bronzes and established that the corrosion resistance of Cu-Al-Fe-Ni bronze is much better than that of Cu-Al-Fe-Mn bronze. Hajek et al [15] established the optimal HT procedure for the highest possible corrosion resistance in Cu-Al-Fe-Mn bronze. Ciurdas et al [16] studied the corrosion resistance of heat-treated Cu-Al-Fe-Mn bronze and reported that the hardened sample showed the best resistance to galvanic corrosion.…”
Section: Refmentioning
confidence: 99%
“…Detailed information about the effects of HT on the microstructure of complex aluminium bronzes is contained in the review paper composed by Brezina [1]. The dependence between the HT parameters and microstructure of individual types of Cu-Al-X bronze with β-transformation has been studied by numerous authors: Cu-9Al-4Fe [3][4][5], Cu-Al-Ni-Fe [6][7][8][9][10][11][12][13][14], Cu-Al-Fe-Mn [11,[15][16][17], Cu-Al-Fe-Be [12]. Changing the microstructure by performing HTs on the complex aluminium bronzes also changes the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%